Speech intelligibility in a patient with an auditory brain stem implant - Šindija, Branka; Mildner, Vesna (2000)
A case study of a 29 year old female patient with auditory brainstem implant (ABI) is presented. Bilateral auditory nerve tumor (neurinoma n. statoacustici) resulting in bilateral deafness (>100 dB) had been diagnosed in 1994. The profound deafness caused psychological problems as well. In January 1995 the tumor on the left side (14 mm) was removed followed by auditory rehabilitation. In January 1999, it became necessary to remove the right auditory nerve tumor. During the surgery the ABI (donated by Cochlear, Basel) was implanted. Extensive auditory rehabilitation started after the first fitting in March, 1999. During the first fitting 15 electrodes with auditive-only sensations were found, but with only three different pitch discrimination areas. In the course of rehabilitation the following parameters were monitored: frequency and intensity discrimination, prosody discrimination and speech intelligibility with and without lip-reading. Speech intelligibility tests included minimum pairs (/kut/- /kat/; /sir/ - /pir/), open and closed set words (days of the week, months), numbers, and sentences with known (previously practiced) and novel (unpracticed) content. A maximum score without lip-reading was reached 6 months after the initial tuning. Maximum intelligibility on known sentences was 96%, on onovel sentences 52%, on closed set words 85% and on open set words 50%. Data on speech intelligibility during a 16-month follow up will be presented. Results are encouraging, although it seems that the patient has reached a plateau and is not progressing at the rate that could be expected based on the initial success. A probable reason could lie in the patient's psychological and social (war refugee) status.
Projekt MZOS
Projekt MZOS
ENG